METTL3 suppresses pyroptosis in obstructive sleep apnea-associated hypertension via YTHDF2-mediated SOX4 mRNA degradation - Wenjun Zhu; Yanyan Hou; Can Yang; Yaping Tian; Linna Cao; Wenjun Li; Liang Xie; Lirong He (Journal of Physiology and Biochemistry, 2026)

Emerging insights into wine polysaccharides: Mechanisms, evolutions and applications in wine flavor management - Zhenyue Yang; Linna Song; Yujie Hao; Nannan Liu; Ziyu Wei; Xiaxia Hou; Yu Gao; Wen Ma (Trends in Food Science & Technology, 2026)

Enhanced biodegradation of sulfaquinoxaline by functional bacteria: Identifying the rate-limiting step, metabolite toxicity, and dissemination risks of antibiotic resistance genes - Linna Zhang; Yuxia Zhao; Sufang Wang; Xin Fan; Aijuan Zhou; Bowei Zhao; Yu Yang; Xiuping Yue; Yanjuan Gao (Journal of Environmental Chemical Engineering, 2026)

Co-exposure of sequential extreme weather and non-biodegradable/biodegradable microplastics (NBMPs/BMPs) on soil bacterial communities and the extracellular polymeric substances (EPS)-extracellular enzyme interaction mechanisms - Xinyu Yang; Yulian Ma; Xin Wang; Yue Sun; Qianzhi Zeng; Yunhong Pu; Bowen Yang; Yaxuan Wu; Xinran Su; Linna Shi; Shuang Li; Wenzhuo Sui; et al. (Journal of Environmental Chemical Engineering, 2026)

Sulfobutylether-(hydroxypropyl-β-cyclodextrin) bonded silica as stationary phase for enhancing chiral separation in liquid chromatography - Linna Xu; Ankang Li; Jialong Wang; Gaosheng Yang; Liqin Lin; Keer Yu; Huizhen Ni; Wentao Xu; Junchao Zhu; Dongping Cheng; Shengqiang Tong (Analytica Chimica Acta, 2026)

DOM-mediated interaction of DOM-enzyme-pollutants affected the toxicity of combined aged tire wear particles (aged-TWPs) and polyfluoroalkyl substances (PFASs) in soil under successive extreme weather stress - Xin Wang; Yulian Ma; Xinyu Yang; Yue Sun; Wenzhuo Sui; Yunhong Pu; Qianzhi Zeng; Yaxuan Wu; Bowen Yang; Xinran Su; Shuang Li; Linna Shi; et al. (Journal of Environmental Management, 2026)

Effects of Perfluoroheptanoic Acid (PFHpA) on Bacterial Community, Elemental Cycling and ARGs Transmission in Sediment - Shengnan Shi; Xinran Su; Linna Shi; Shuang Li; Yunhong Pu; Qianzhi Zeng; Bowen Yang; Yaxuan Wu; Yue Sun; Yulian Ma; Xinyu Yang; Xin Wang; et al. (Water, Air, & Soil Pollution, 2026)

Multifunctional extreme-temperature-tolerant photonic electronic skin for synergistic electrical and optical sensing - Jun-Tao Liu; Linna Huang; Zimo Zhang; Shulin Qin; Jia-Li Xu; Yufan Zhang; Chen Yang; Yu Tian (Chemical Engineering Journal, 2026)

Divergent biodegradation responses to single and combined antibiotic exposure in a simultaneous denitrification and methanogenesis system: Impacts on microbial community structure, metabolite dynamics, and resistome - Fang Yang; Linna Zhang; Sufang Wang; Jierong Zheng; Aijuan Zhou; Yu Yang; Xiuping Yue; Bowei Zhao; Yanjuan Gao (Journal of Environmental Chemical Engineering, 2026)

Insights into low temperature adaptation in Epinephelus awoara through integrated genome and transcriptome analysis - Linna Wang; Shuai Chen; Zhentong Li; Yang Liu; Shihao Wang; Tangtang Ding; Fengfan Yang; Chunbai Zhang; Linlin Li; Wensheng Li; Qingbin Wang; Xia Zhao; et al. (Aquaculture, 2026)

Quasi-pure-phase 2D perovskites for high-efficiency and stable 2D/3D perovskite heterojunction solar cells - Fei Wu; Yuping Gao; Ye Zeng; Junhong Tan; Cheng Zhong; Xing Gao; Yingguo Yang; Yongsheng Liu; Linna Zhu (Chemical Engineering Journal, 2025)

Embryonic and Larval Development of an Interspecific Grouper Backcross Between the Kelp Grouper (Epinephelus moara) ♀ and KGGG (E. moara ♀ × E. lanceolatus ♂) ♂ - Yidan Xu; Yongsheng Tian; Shihao Wang; Tangtang Ding; Linna Wang; Zhentong Li; Linlin Li; Yang Liu (Fishes, 2025)
Backcrossing serves as an effective tool for interspecific gene introgression, facilitating germplasm improvement. To develop superior grouper aquaculture varieties, in this study, a backcrossed breed was constructed by crossing a male hybrid grouper, KGGG (Epinephelus moara ♀ × E. lanceolatus ♂), with a female parent kelp grouper (KG; E. moara). Here, we observed embryonic, larval development, and morphological changes in KG × KGGG. Additionally, the total length and body weight of the backcrossed breed and maternal parent were compared at 160 d post hatching (dph). The results showed that fertilization and the hatching rate were 73.23 ± 4.23% and 51.74 ± 3.67%, respectively, and the egg size was 0.89 ± 0.03 mm. Hatching occurred 23:19 h after fertilization at 25 ± 1 °C, and the newly hatched larvae were 1.94 ± 0.13 mm in length. Furthermore, at 160 dph, the total length and body weight of the backcrossed breed were 1.2-fold and 1.9-fold greater, respectively, when compared with those of the maternal parent. Importantly, it is possible that backcrossed KG × KGGG could become a dominant strain in grouper aquaculture practices.

Compartment-specific core microbiomes and functions in rice - Linna Ma; Yusha Bai; Xiang Li; Jingyu Li; Feixue Li; Yan Yue; Yingguang Li; Jingwen Guo; Chen Ye; Xinyue Mei; Fei Du; Yixiang Liu; et al. (Plant and Soil, 2025)

UGPase: A novel molecule that regulates LPS synthesis, virulence, and immunogenicity of Brucella melitensis - Si Chen; Yuxin Liu; Yang Gao; Dong Zhang; Ru Zhang; Fei Tu; Nan Li; Qingkui Jiang; Linna Liu; Yanling Yang (Veterinary Microbiology, 2025)

Pregnancy-induced changes in the toll-like receptor pathway in the ovine duodenum - Linna Gao; Haiquan Ding; Qianqian Shi; Xinxin Wang; Leying Zhang; Ling Yang (Veterinary Immunology and Immunopathology, 2025)

Novel anionic functionalized magnetic β-cyclodextrin composites with excellent adsorption capacity for moxifloxacin and wide pH adaptive adsorption capability for copper ion - Erming Ouyang; Linna Ye; Wenhao Zhang; Rui Zhao; Hongwei Yang; Suting Deng; Yuxiang Xiong; Xinhui Hu; Ziyue Zhou (Environmental Research, 2025)

Toward crop–livestock integration: a comprehensive framework for cropping system adaptation assessment to mitigate forage shortage - Dan Liu; Jianjun Jin; Xin Qiu; Rui He; Linna Li; Jie Yang (Environment, Development and Sustainability, 2024)

Niche-specific evolution and gene exchange of Salmonella in retail pork and chicken - Huanjing Sheng; Linna Zhao; Jia Suo; Qiuping Yang; Chenyang Cao; Jia Chen; Guangqing Cui; Yiling Fan; Yi Ma; Shengnan Huo; Xin Wu; Tao Yang; et al. (Food Research International, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

TaSRT2 recognizes a viral protein to activate host immunity by increasing histone acetylation - Kaili Zhong; Yaoyao Jiang; Haichao Hu; Bowen Yuan; Mila Wu; Aizhu Tu; Gecheng Xu; Linna Cai; Tingting Liu; Shiqi Gao; Linzhi Li; Qiansheng Liao; et al. (Science Bulletin, 2024)

The potential impact of 6PPD and its oxidation product 6PPD-quinone on human health: A case study on their interaction with human serum albumin - Chaolan Chen; Linna Gao; Pei Ding; Shuyuan Zhang; Xiaowei Wang; Kaiyu Yang; Yikun Zhou; Baozhu Chi; Xun Tuo (Chemosphere, 2024)

Early pregnancy modulates the expression of interferon-stimulated genes, progesterone receptors, and progesterone-induced blocking factor in ovine duodenum - Leying Zhang; Shuxin Zhao; Guoao Yu; Linna Gao; Mengyao Song; Ling Yang (Small Ruminant Research, 2024)

Network pharmacology combined with molecular docking and molecular dynamic simulation to reveal the potential mechanism of lentinan ameliorating hyperlipidemia - Zhongxing Chu; Linna Zeng; Feiyan Yang; Zuomin Hu; Yi Luo; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

Steep oceanic DIC δ13C depth gradient during the Hirnantian Glaciation - Shengchao Yang; Junxuan Fan; Thomas J. Algeo; Graham A. Shields; Ying Zhou; Chao Li; Jitao Chen; Weiqiang Li; Na Li; Jian Cao; Linna Zhang; Zongyuan Sun; et al. (Earth-Science Reviews, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Zn-assisted low-temperature reconstruction of NiCo heterogeneous catalysts for lithium-oxygen batteries - Yuan Yang; Jianwei Qiu; Linna Dai; Zhibiao Hu; Xiaohang Lin; Minghao Hua; Pengchao Si (Chemical Engineering Journal, 2024)

Comparative transcriptome analysis of hybrid Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) and Epinephelus fuscoguttatus under temperature stress - Pengfei Duan; Yongsheng Tian; Zhentong Li; Shuai Chen; Linlin Li; Xinyi Wang; Linna Wang; Yang Liu; Jieming Zhai; Wensheng Li; Qingbin Wang; Wenhui Ma; et al. (Aquaculture, 2024)

Mutant p53R211* ameliorates inflammatory arthritis in AIA rats via inhibition of TBK1-IRF3 innate immune response - Yaling Zeng; Jerome P. L. Ng; Linna Wang; Xiongfei Xu; Betty Yuen Kwan Law; Guobing Chen; Hang Hong Lo; Lijun Yang; Jiujie Yang; Lei Zhang; Liqun Qu; Xiaoyun Yun; et al. (Inflammation Research, 2023)
Background Rheumatoid arthritis (RA) is an autoimmune inflammation disease characterized by imbalance of immune homeostasis. p53 mutants are commonly described as the guardian of cancer cells by conferring them drug-resistance and immune evasion. Importantly, p53 mutations have also been identified in RA patients, and this prompts the investigation of its role in RA pathogenesis. Methods The cytotoxicity of disease-modifying anti-rheumatic drugs (DMARDs) against p53 wild-type (WT)/mutant -transfected RA fibroblast-like synoviocytes (RAFLSs) was evaluated by MTT assay. Adeno-associated virus (AAV) was employed to establish p53 WT/R211* adjuvant-induced arthritis (AIA) rat model. The arthritic condition of rats was assessed by various parameters such as micro-CT analysis. Knee joint samples were isolated for total RNA sequencing analysis. The expressions of cytokines and immune-related genes were examined by qPCR, ELISA assay and immunofluorescence. The mechanistic pathway was determined by immunoprecipitation and Western blotting in vitro and in vivo. Results Among p53 mutants, p53 R213* exhibited remarkable DMARD-resistance in RAFLSs. However, AAV-induced p53 R211* overexpression ameliorated inflammatory arthritis in AIA rats without Methotrexate (MTX)-resistance, and our results discovered the immunomodulatory effect of p53 R211* via suppression of T-cell activation and T helper 17 cell (Th17) infiltration in rat joint, and finally downregulated expressions of pro-inflammatory cytokines. Total RNA sequencing analysis identified the correlation of p53 R211* with immune-related pathways. Further mechanistic studies revealed that p53 R213*/R211* instead of wild-type p53 interacted with TANK-binding kinase 1 (TBK1) and suppressed the innate immune TBK1–Interferon regulatory factor 3 (IRF3)–Stimulator of interferon genes (STING) cascade. Conclusions This study unravels the role of p53 R213* mutant in RA pathogenesis, and identifies TBK1 as a potential anti-inflammatory target.

A high-resolution record of the late Hirnantian to Aeronian marine redox change in South China and its relationship with the record of graptolite biodiversity - Zongyuan Sun; Fangqi Zhao; Michael J. Melchin; Junxuan Fan; Bolin Zhang; Xin Jin; Zihu Zhang; Shengchao Yang; Qing Chen; Yiying Deng; Linna Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Effect of non-permeable cryoprotectant sucrose on the development of spotted knifejaw (Oplegnathus punctatus) embryos - Linlin Li; Yongsheng Tian; Zhentong Li; Pengfei Duan; Xinyi Wang; Shuai Chen; Linna Wang; Yang Liu; Qingbin Wang; Wensheng Li; Xia Zhao; Wenhui Ma; et al. (Cryobiology, 2023)

Metagenomics insights into the functional profiles of soil carbon, nitrogen, and phosphorus cycles in a walnut orchard under various regimes of long-term fertilisation - Tianyu Du; Qufei Hu; Wenjing Mao; Zhou Yang; Hong Chen; Linna Sun; Meizhi Zhai (European Journal of Agronomy, 2023)

Mixed-linker MOFs-derived cross-linked copolymer electrolyte enables high lithium mobility for dendrite-free all-solid-state batteries - Jia Zhou; Xingfa Zeng; Linna Dong; Liya Chen; Xiangrong Wei; Yang liu; Liyi Shi; Le Yu; Jifang Fu (Chemical Engineering Journal, 2023)

Assessing nickel sector index volatility based on quantile regression for Garch and Egarch models: Evidence from the Chinese stock market 2018–2022 - Linna Lu; Yalin Lei; Yang Yang; Haoqi Zheng; Wen Wang; Yan Meng; Chunhong Meng; Liqiang Zha (Resources Policy, 2023)

Long-term organic fertilizer and biofertilizer application strengthens the associations between soil quality index, network complexity, and walnut yield - Tianyu Du; Qufei Hu; Haiyun He; Wenjing Mao; Zhou Yang; Hong Chen; Linna Sun; Meizhi Zhai (European Journal of Soil Biology, 2023)

Heterosis in growth and low temperature tolerance in Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) - Shuai Chen; Yongsheng Tian; Zhentong Li; Yang Liu; Ziqi Li; Pengfei Duan; Linlin Li; Xinyi Wang; Linna Wang; Xinlei He; Xia Zhao; Wensheng Li; et al. (Aquaculture, 2023)

The effect of underwater supplemental light on the growth of V.spinulosa Yan and the restoration process of water - Jinshan Zhao; Pu Yang; Yuye Lin; Xiaoyao Zhu; Jiaxin Wang; Xinyu Gan; Xiangyong Zheng; Min Zhao; Chunzhen Fan; Linna Du; Huanyi Miu (Process Safety and Environmental Protection, 2023)

Decoupling analysis of China's mining industrial development and water usage: Based on production-based and consumption-based perspectives - Yiming Li; Yingnan Zhang; Lin Yang; Fenglian Du; Linna Sai; Bin Zhang (Journal of Cleaner Production, 2023)

Genome-wide analysis of CtNF-YB and lipid synthesis regulation of CtNF-YB12 in Carthamus tinctorius L. - Sinan Deng; Ruinan Wang; Chenlu Tao; Lixia Li; Shuai Wang; Chang Jia; Yilin Liu; Ruo Du; Linna Du; Jing Yang (Plant Cell Reports, 2023)

Exploring the urban-rural development differences and influencing factors in the Huang-Huai-Hai Plain of China - Mingyang Cheng; Linna Li; Yang Zhou (Journal of Geographical Sciences, 2020)

Geochemical behaviors of antimony in mining-affected water environment (Southwest China) - Ling Li; Han Tu; Shui Zhang; Linna Wu; Min Wu; Yang Tang; Pan Wu (Environmental Geochemistry and Health, 2019)

Using magnetic susceptibility to evaluate pollution status of the sediment for a typical reservoir in northwestern China - Huiyun Pan; Xinwei Lu; Kai Lei; Dongqi Shi; Chunhui Ren; Linna Yang; Lijun Wang (Environmental Science and Pollution Research, 2019)

Combining multi-source data to explore a mechanism for the effects of micrometeorological elements on nutrient variations in paddy land water - Hezhen Lou; Shengtian Yang; Changsen Zhao; Zhiwei Wang; Xiaolin Liu; Liuhua Shi; Linna Wu; Fanghua Hao; Mingyong Cai (Paddy and Water Environment, 2017)

Accumulation and source of heavy metals in sediment of a reservoir near an industrial park of northwest China - Yuanjie Zhu; Xinwei Lu; Linna Yang; Lijun Wang (Frontiers of Earth Science, 2016)

Suitable hepatitis B vaccine for adult immunization in China - Linna Yang; Jun Yao; Jing Li; Yongdi Chen; Zheng-gang Jiang; Jing-jing Ren; Kai-jin Xu; Bing Ruan; Shi-gui Yang; Bing Wang; Tian-sheng Xie; Qian Li (Immunologic Research, 2016)

Evaluating the suitability of TRMM satellite rainfall data for hydrological simulation using a distributed hydrological model in the Weihe River catchment in China - Haigen Zhao; Shengtian Yang; Zhiwei Wang; Xu Zhou; Ya Luo; Linna Wu (Journal of Geographical Sciences, 2015)

One-step integration of multiple genes into the oleaginous yeast Yarrowia lipolytica - Shuliang Gao; Linna Han; Li Zhu; Mei Ge; Sheng Yang; Yu Jiang; Daijie Chen (Biotechnology Letters, 2014)

The effect of environmental factors on spatial variability in land use change in the high-sediment region of China’s Loess Plateau - Ya Luo; Shengtian Yang; Changsen Zhao; Xiaoyan Liu; Changming Liu; Linna Wu; Haigen Zhao; Yichi Zhang (Journal of Geographical Sciences, 2014)

A DEAD-box RNA helicase produces two forms of transcript that differentially respond to cold stress in a cryophyte (Chorispora bungeana) - Yu Yang; Zhenglong Sun; Chenchen Ding; Linna Ge; Likun Sun; Muqun Bai; Yuan Song; Shuyan Chen; Lizhe An (Planta, 2014)

Progresses on microwave remote sensing of land surface parameters - JianCheng Shi; Yang Du; JinYang Du; LingMei Jiang; LinNa Chai; KeBiao Mao; Peng Xu; WenJian Ni; Chuan Xiong; Qiang Liu; ChenZhou Liu; Peng Guo; et al. (Science China Earth Sciences, 2012)